Synthesis and Molecular Docking Study of Dibenzal Monocarbonyl (Curcumin Analog) and Its Potential as Anti-Inflammatory - Minandre Wiratama; Cornelia Budimarwanti (Jurnal Kimia Sains dan Aplikasi, 2025)
Curcumin is a naturally occurring substance with a wide range of biological activity. One of the biological activities of curcumin is as an anti-inflammatory. The science of organic synthesis is able to produce substances that are analogous to those found in nature. The synthesis of organic compounds can also be used to change a compound by making it more bioactive. This research focused on synthesizing dibenzal monocarbonyl, a compound similar to curcumin, and examined its interaction with the active site of cyclooxygenase-2 (COX-2) through molecular docking simulations. Dibenzal monocarbonyl was synthesized via an aldol condensation reaction utilizing sodium hydroxide as a catalyst. The synthesized compound was characterized using FTIR and 1H-NMR, achieving a yield of 98.676%. Molecular docking was performed utilizing AutoDock Tools and AutoDock Vina, and each docked compound was visualized through Discovery Studio Visualizer. This compound demonstrated the highest anti-inflammatory activity against COX-2, as indicated by molecular docking studies, with a binding affinity of -8.4 kcal/mol.